2021
DOI: 10.3390/ijms222313133
|View full text |Cite
|
Sign up to set email alerts
|

Control of TRPM3 Ion Channels by Protein Kinase CK2-Mediated Phosphorylation in Pancreatic β-Cells of the Line INS-1

Abstract: In pancreatic β-cells of the line INS-1, glucose uptake and metabolism induce the openings of Ca2+-permeable TRPM3 channels that contribute to the elevation of the intracellular Ca2+ concentration and the fusion of insulin granules with the plasma membrane. Conversely, glucose-induced Ca2+ signals and insulin release are reduced by the activity of the serine/threonine kinase CK2. Therefore, we hypothesized that TRPM3 channels might be regulated by CK2 phosphorylation. We used recombinant TRPM3α2 proteins, nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Both TRPA1 and TRPV1 can be phosphorylated and sensitized by calcium–calmodulin-dependent protein kinase II (CaMKII) and protein kinase C (PKC) ( Bonnington and McNaughton, 2003 ; Zhang et al, 2010 ; Wang et al, 2015 ; Patil et al, 2020 ). Since TRPM3 proteins also harbor several potential phosphorylation sites ( Becker et al, 2021 ), we examined the effect of inhibitors of either CaMKII (KN62; 1 μM; Figure 4A ) or PKC (Gö6983; GÖ; 1 μM, Figure 4D ) on TRPM3 sensitization by BK. Interestingly, neither inhibition of CaMKII ( p < 0.001, Mann-Whitney U; Figure 4B ) nor PKC ( p < 0.01, Mann-Whitney U; Figure 4E ) prevented TRPM3 sensitization.…”
Section: Resultsmentioning
confidence: 99%
“…Both TRPA1 and TRPV1 can be phosphorylated and sensitized by calcium–calmodulin-dependent protein kinase II (CaMKII) and protein kinase C (PKC) ( Bonnington and McNaughton, 2003 ; Zhang et al, 2010 ; Wang et al, 2015 ; Patil et al, 2020 ). Since TRPM3 proteins also harbor several potential phosphorylation sites ( Becker et al, 2021 ), we examined the effect of inhibitors of either CaMKII (KN62; 1 μM; Figure 4A ) or PKC (Gö6983; GÖ; 1 μM, Figure 4D ) on TRPM3 sensitization by BK. Interestingly, neither inhibition of CaMKII ( p < 0.001, Mann-Whitney U; Figure 4B ) nor PKC ( p < 0.01, Mann-Whitney U; Figure 4E ) prevented TRPM3 sensitization.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have found that [Ca2+] cyt and intracellular Mg2+ ions inhibit the activity of TRPM3 channels. 77 , 91 …”
Section: Activation Mechanisms Of the Trpm Channelsmentioning
confidence: 99%
“…Further, in other circumstances, CK2 can phosphorylate substrates that do not share the consensus sequence, such as serine 392 of p53 or the tyrosine residues of Fpr3 in yeast [ 120 , 121 , 122 ]. Due to the versatility of this enzyme, CK2 activates numerous interacting proteins, such as nicotinamide adenine dinucleotide phosphate (NADPH) oxidase 1 and transient receptor potential cation channel subfamily M (TRPM) 3 ion channels [ 123 , 124 ]. As CK2 targets many substrates, it has increasingly become a candidate for novel therapeutics, as it is implicated in the progression of many diseases, such as breast and colon cancer [ 23 , 125 , 126 , 127 ].…”
Section: Ck2 Structure and Kinase Activitymentioning
confidence: 99%